“Pelas ruas de Belém...”: produção de sentido e dinâmica cultural nos arrastões do Pavulagem em Belém do Pará - CHAGAS JUNIOR, Edgar Monteiro (Universidade Federal do Pará, 2017)
Recent demands by groups of residents from large Brazilian urban centers for some cultural manifestations understood as traditional – approached according to a model of cultural representation whose dimension of identity value has been increasingly activated – has permitted some reflections that surpass the conditions of use and appropriation of urban public spaces that elaborate and institute different forms of artistic- cultural expression without necessarily following the consolidated standards for large events where distance from the artist and the public prevails. During the last two decades, there has been a resuming of actions of pedagogical nature on knowledge whose origin are in old popular dances that started to provide a referential for production of discourses by urban cultural activists who became known for their appeal to “degradation” of identities in a world economically globalized, redirecting participation and consumption of the socalled cultural assets and providing a form of public mobilization that began to (re) assume the streets as referential in the sense of socialization and experimentation as driving energy of accomplishment of a cultural action performatically ritualized. Therefore, this study aims to collaborate with these discussions anchored in the possibility of intermingling among the notions of heritage, ritual and performance motivated by observations of a cultural movement called Arrastão do Pavulagem, which has been performing for the last twenty eight years, and has been consolidated in the annual cultural schedule of Belém do Pará as a moment of esthetic and symbolic (re) creation of the festivity based on performance of musicians, dancers, actors, producers who carry out their actions in an environment, that suggests that it is institutionalized from a sense of participation and experimentation of the place as one of the fundaments of this movement mobilized by different interests, but that, when meeting at this environment, intermingle and performatically elaborate discourses and visualities that operate in the possibility of (re) interpretation of the urban landscape of the Historical Center of Belém do Pará.